The ancient mediterranean values of ''honour and shame'' as a hermeneutical lens of reading the book of Job - Mbuvi, Andrew Mũtũa (Old Testament essays, 2010)
The book of Job is here read through the ancient Near Eastern values of honour and shame and also in relationship to its placing within Wisdom literature. This article points out the fact that the book of Job goes beyond focus of wisdom whose primary concern is navigating life successfully. For Job, it is the concern of what Gustavo Guttiérez calls disinterested faith that puts God's honour at the centre of his struggles.